A continent moving West? EU enlargement and labour migration from Central and Eastern Europe (Amsterdam, 2010)
"A Continent Moving West? argues that the conceptualization of migration as a one-way or long-term process is becoming increasingly wide of the mark. Rather, east-west labor migration in Europe, in common perhaps with other flows in and from other parts of the world, is diverse, fluid, and influenced by the dynamics of local and sector-specific labor markets and migration-related political regulations.